PUBLISHING WHITENESS: RACIAL AUTHORSHIP, CULTURAL APPROPRIATION, AND MARKET-DRIVEN MULTICULTURALISM IN R.F. KUANG’S YELLOWFACE - Traesar, Livia (Rubikon : Journal of Transnational American Studies, 2026)
This article examines how R. F. Kuang’s Yellowface portrays the contemporary U.S. publishing Industry as a racialized system shaped by market-driven diversity discourse. Although publishing institutions increasingly promote diversity, questions remain about whether such initiatives distribute narrative authority or merely repackage inequality. The research addresses this problem by analyzing how the novel represents authorship, cultural appropriation, and institutional legitimacy. Drawing on whiteness studies, symbolic annihilation, and neoliberal multiculturalism, this research employs a qualitative interpretive method based on close textual reading. The findings reveal that diversity in the novel functions primarily as a market strategy rather than a transformative commitment. Minority narratives remain commercially valuable even when minority authorship is displaced, while whiteness continues to operate as an invisible norm that authorizes representation. The analysis also demonstrates how controversy, rebranding, and performative identity sustain institutional power within an attention-driven cultural economy. These dynamics show that inclusion can coexist with dispossession when authority over storytelling remains unevenly distributed. This article contributes to scholarship on contemporary cultural production by positioning Yellowface as a critique of neoliberal diversity discourse’s reshaping of authorship and legitimacy in the twenty-first-century publishing industry.